The Nephroprotective Activity of Boesenbergia Rotunda Rhizome by Reducing Creatinine, Urea Nitrogen, Glutamic Pyruvic Transaminase, and Malondialdehyde Levels in the Blood and Attenuating the Expression of Havcr1 (KIM-1), Lcn2 (NGAL), Casp3, and Casp7 Genes in the Kidney Cortex of Cisplatin-Induced Sprague-Dawley Rats - Sujana D; Sumiwi SA; Saptarini NM; Levita J (Dove Medical Press, 2024)
Dani Sujana,1,2,* Sri Adi Sumiwi,1,* Nyi Mekar Saptarini,3,* Jutti Levita1,* 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 46363, Indonesia; 2Diploma Program of Pharmacy, Karsa Husada Garut College of Health Sciences (Stikes Karsa Husada Garut), Garut, West Java, 44151, Indonesia; 3Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 46363, Indonesia*These authors contributed equally to this workCorrespondence: Jutti Levita, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 46363, Indonesia, Tel +6222-84288888 Ext 3510, Email jutti.levita@unpad.ac.idBackground: Cisplatin chemotherapy induces nephrotoxicity by producing reactive oxygen species, hence, discovering add-on nephroprotective drugs for patients with cancer is challenging. Boesenbergia rotunda has been reported for its antioxidant properties.Purpose: This study aims to explore the nephroprotective mechanism of the ethanol extract of Boesenbergia rotunda rhizome (EEBR) in cisplatin-induced rats.Methods: The rats were randomly assigned into 6 groups: the normal control (treated with saline); the negative control (cisplatin-induced without any treatment); the positive control (treated with quercetin 50 mg/kg BW); and 3 treatment EEBR (125 mg/kg BW; 250 mg/kg BW; 500 mg/kg BW) groups for 10 days. The % relative organ weight, kidney histopathology, and nephrotoxicity biomarkers expression were evaluated.Results: EEBR decreased creatinine, urea nitrogen, glutamic pyruvate transaminase, and malondialdehyde levels in the blood of cisplatin-induced rats. An insignificant increase in GOT was observed in rats treated with the highest dose of EEBR. EEBR did not significantly alter the BW and the % kidney relative weight. An abnormal shape of the Bowman capsule is observed in the negative control group. EEBR reduced the expression of Havcr1 (KIM-1), Lcn2 (NGAL), Casp3, and Casp7 genes in rats' kidneys.Conclusion: Boesenbergia rotunda could be considered a potential candidate for add-on therapy in cisplatin-treated patients, but further studies are needed to verify its efficacy and safety.Keywords: acute kidney injury, boesenbergia rotunda, medicinal plants, nephroprotective activity, Zingiberaceae